(untitled) (American Journal of Business Management, Economics and Banking, 2026)
In recent decades, the global tourism market has been developing rapidly, and competition between countries in attracting tourist flows has significantly increased. The tourism sector is considered not only as a service sector, but also as one of the important drivers of the national economy. According to the World Tourism Organization, the tourism sector forms a significant part of the global gross domestic product and plays an important role in creating millions of jobs. Therefore, many countries, considering tourism as one of the priority areas of economic development, are paying special attention to improving the mechanisms for strategic management of this sector.